The Modal Split of Cities: A Workplace‐Based Mixed Modelling Perspective. (10th November 2014) - Vanoutrive, Thomas
Abstract: Many transport planners and policy‐makers compare cities on the basis of travel behaviour or transport system characteristics. These comparisons are then used to promote cities as 'cycling capitals' or 'public transport paradises'. However, data‐related and methodological issues make comparisons across cities difficult. This paper presents an alternative to the dominant atomistic‐residential perspective which takes a random sample of residents in a city as input. We conceptualise cities as concentrations of workplaces and compare the commuting behaviour of employees active in a selection of sectors. This paper presents a new indicator to measure the modal split of cities and explains the level of car use in Belgian cities using mixed models. The presence of a railway station is associated with lower levels of car use, while highway access increases the share of the car. The car is also less popular in city centres, subcentres and in more dense urban areas.